Development of a Multidimensional Scale of Family Expressed Emotion (MS-FEE) for Type 2 Diabetes Mellitus outpatients - Nida Ul Hasanat; Ramadhan Dwi Marvianto; Alfan Fahri Rifqi As Sidqi; Anke Karl (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Family expressed emotion (FEE) affects self-management in people with Type 2 Diabetes Mellitus (T2DM), but a measurement instrument based on the Indonesian cultural context has yet to be made available. This study aims to develop a self-report FEE scale for individuals with Type 2 Diabetes Mellitus, involving 229 participants in Yogyakarta, Indonesia. The items were developed from five dimensions of expressed emotion (EE) and selected through expert validation and construct validity testing using confirmatory factor analysis (CFA). The results showed that the five-correlated factor model was the best fit (CFI = .959, TLI = .948, RMSEA = .042, SRMR = .050, BIC = 9,283.594). The reliability coefficients obtained using McDonald’s ω were acceptable, ranging from .603 to .761, apart from emotional over-involvement, which only scored .569. MIMIC-based DIF analysis by gender flagged 1 item (β = .220), indicating that women had higher endorsement, while other items were invariant. The findings confirm that FEE is multidimensional, especially in communities with a collectivist culture. The practical implication is that the scale can be used in clinical assessment and family-based interventions to enhance the self-management of T2DM patients in Indonesia.